Physico-Chemical Characteristics of Roselle (Hibiscus Sabdariffa L.) Calyx and Effect of Processing and Storage on the Stability of Anthocyanins in Roselle Juice - Wong, Peng Kong (2002)
The main purpose of this project was to focus on determining the physicochemical properties of roselle calyx, to develop a processing method that would optimise the colour stability and determining the influences of different treatments on roselle juice during storage. The physico-chemical characteristics of roselle included size, weight, pH, titratable acidity, soluble solids, anthocyanin contents, colour density, polymeric colour, percent polymeric colour and browning index were studied. Succinic acid and glucose were the major organic acid and sugar found present in roselle with 0.51 g/100g and 1.29 g/100g, respectively. The most biologically effective natural antioxidant vitamins such as ascorbic acid, p-carotene and lycopene were also determined and quantified by high performance liquid chromatography (HPLC). The amounts of ascorbic acid, p-carotene and lycopene contents were 141.09 mg/100g, 1.88 mg/100g and 164.34 mg/100g, respectively. Two main anthocyan ins namely delphinidin-3-sambubioside and cyanidin-3- sambubioside were present in roselle detected by thin layer chromatography (TLC) and HPLC. The optimum conditions for hot water extraction (HWE) of roselle juice was determined by using Response Surface Methodology (RSM). Time-temperature combinations in the range of 30-300 minutes and 30-90°C were the independent variables and their effects on anthocyanins content, colour density and ascorbic acid were evaluated The results implied an optimum juice extraction condition for HWE to be at 3.5 hours at 60°C. The juice obtained from HWE method was then compared with juices obtained from hot water blending (HWB) method, cold water blending (CWB) method and screw press (SP) method for their physico-chemical characteristics and sensory evaluation. Results of the study indicated that HWE method was found to be the most effective extraction method resulting in high anthocyanins content and ascorbic acid. Sensory evaluation also showed that juice obtained from HWE method was higher in quality in termed of taste, colours and flavour. Juice produce through SP method was poor in quality and sensory result compare with other. Four different treatments were given to the sample roselle juice: control (no additions), ascorbic acid, cysteine hydrochloride and sodium metabisulphite. The influence of storage at 4 ± 2°C, 27 ± 2°C and 40 ± 2°C was investigated. Losses in anthocyanins and ascorbic acid were very small during 12 weeks storage at 4°C as compared to 27°C and 40°C. Higher temperature caused anthocyanin degradation more rapidly. The addition of sodium metabisulphite in roselle juice slowed down the loss of anthocyanins and correspondingly decreased the rate of polymeric colour.Addition of cysteine hydrochloride had only slight effect on colour stability and addition of ascorbic acid seemed to increase the degradation on anthocyanin contents. Addition of cysteine hydrochloride in roselle juice prevents ascorbic acid loss during storage.